Implementasi Edukasi Kebersihan Tangan Sebagai Upaya Meningkatkan Kemandirian Siswa di Kelas IV SD Negeri 3 Taman Bali - Ni Kadek Febriani; Ni Putu Eni Astuti (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This community service activity aims to increase awareness and independence of elementary school students in maintaining hand hygiene through education on proper handwashing. The background to this activity stems from the low level of handwashing habits among school-age children, despite hand hygiene being a simple action that has a significant impact on preventing infectious diseases. Based on initial observations at Tamanbali 3 Public Elementary School, most students did not yet have the habit of washing their hands before eating or after playing, despite the availability of facilities. Therefore, a hand hygiene education program was implemented, designed to help students understand the importance of proper handwashing according to WHO guidelines. The activity methods included outreach through educational posters and videos, demonstrations of the seven steps of handwashing, mentoring in daily habits, and evaluation of behavioral changes. The results of the activity showed a significant improvement in students' hand hygiene behavior. Students began washing their hands independently before eating and after activities without being reminded by teachers. The school environment also became cleaner and healthier due to the growing awareness of personal hygiene among students. Teachers and the school are committed to continuing this habit as part of the daily classroom routine. This activity demonstrates that hand hygiene education delivered through interactive methods can shape character and hygiene habits from an early age.